Comparison of steroid nasal irrigation and normal saline irrigation following endoscopic sinus surgery in patients with chronic rhinosinusitis: a prospective randomized study - Sridhar, M. Rama; Niharika, S.; Teja, P. Sai (International Journal of Research in Medical Sciences, 2026)
Background: Postoperative nasal irrigation is an integral component of care following endoscopic sinus surgery (ESS) in patients with chronic rhinosinusitis. Although normal saline irrigation is routinely used, evidence regarding the additional benefit of steroid nasal irrigation in the Indian rural population remains limited. This study aimed to compare the effectiveness of steroid nasal irrigation with normal saline irrigation in the postoperative management of ESS. Methods: This prospective randomized study was conducted over 18 months at a tertiary care center in rural Telangana. Eighty adult patients with chronic rhinosinusitis refractory to medical management who underwent ESS were randomized into two groups: normal saline irrigation (n=40) and steroid nasal irrigation (n=40). Postoperative outcomes were assessed at 2 weeks and 2 months using the Sino-Nasal Outcome Test-22 (SNOT-22) and the Lund–Kennedy endoscopic scoring system. Crust formation, compliance, and adverse effects were also evaluated. Statistical analysis was performed using chi-square and t-tests, with p<0.05 considered significant. Results: Baseline demographic characteristics and disease duration were comparable between groups (p>0.05). Both groups showed significant postoperative improvement; however, the steroid group demonstrated significantly lower mean SNOT-22 scores at 2 weeks (24.95±8.38 vs 37.90±4.30; p<0.001) and 2 months (17.75±6.39 vs 28.53±3.57; p<0.001). Endoscopic assessment revealed significantly greater improvement in Lund–Kennedy scores and reduced crust formation in the steroid group at both follow-up intervals (p<0.001). Compliance was better in the steroid group, with no significant difference in adverse effects. Conclusion: Steroid nasal irrigation following ESS offers superior symptomatic and endoscopic outcomes compared to normal saline irrigation, without increasing adverse effects, and may be considered an effective adjunct in postoperative management.